2016
DOI: 10.1007/s10840-016-0146-1
|View full text |Cite
|
Sign up to set email alerts
|

Proof of concept study: renal sympathetic denervation for treatment of polymorphic premature ventricular complexes

Abstract: Polymorphic PVCs refractory to medication therapy may be modifiable by RSD in patients without structural heart disease. Although encouraging, our data are preliminary and need to be validated in a large population and in long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 33 publications
0
30
0
Order By: Relevance
“…At this point, the results of the proof-of-concept trial SPYRAL HTN-OFF MED suggest efficacy of RDN on BP in the absence of antihypertensive medications [13, 28]. Modulation of the sympathetic nervous system by RDN has been associated with reductions in left ventricular mass, improvements in obstructive sleep apnea severity, and occurrence of arrhythmias [3, 2932]. A pilot study also demonstrated improved compliance measured by PWV after RDN, suggesting that these parameters better reflect the risk of later cardiac events than the reduction in SBP [33].…”
Section: Discussionmentioning
confidence: 99%
“…At this point, the results of the proof-of-concept trial SPYRAL HTN-OFF MED suggest efficacy of RDN on BP in the absence of antihypertensive medications [13, 28]. Modulation of the sympathetic nervous system by RDN has been associated with reductions in left ventricular mass, improvements in obstructive sleep apnea severity, and occurrence of arrhythmias [3, 2932]. A pilot study also demonstrated improved compliance measured by PWV after RDN, suggesting that these parameters better reflect the risk of later cardiac events than the reduction in SBP [33].…”
Section: Discussionmentioning
confidence: 99%
“…Patients still in AF at the end of the procedure were converted to sinus rhythm by cardioversion. And the RSD procedure has been described in detail previously [25]. The patients remained hospitalized in the ward for 24 h after the procedure.…”
Section: Letters To the Editor | 25mentioning
confidence: 99%
“…A 3-channel recorder was used to record the electrocardiographic traces, calculate the minimum, mean and maximum HR, the quantity and the morphologies of PVCs at baseline [8]. Polymorphic PVCs were defined as 3 or more PVCs of different morphologies in a high incidence each one [8].…”
Section: -Hour-holter Monitoringmentioning
confidence: 99%